KEUNGGULAN KOMPARATIF-KOMPETITIF DAN STRATEGI KEMITRAAN - SAPTANA - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
Change of strategic environment in the form of economic globalization, decentralization,change of consumer preference and sustainability of environment, claiming the existence of changeand also adjustment operate institution of agriculture. This article is addressed to study statuscomparative and competitive advantage some agriculture commodities, partner of business agricultureperformance, and revitalization institution of agriculture to realize comparative advantage becomecompetitive advantage through partner business strategy. Status comparative and competitiveadvantages show though most agriculture commodities till in this time remain to have comparative andcompetitive advantage, but advantages had progressively lower and rentan to change of external, withcoefficient value of DRCR and of PCR come near number 1 (one). Until so far not yet been woke upby institution partner of business which each other requiring, each other strengthening, and each otherprofiting, and also the nature of partner which do not have sustainable. Several weakness for exampleis lowering him of commitment among which was have partner, position bargaining not equality, andalso less him in pricing and division of added value or profit margin. Institution partnership ofbusiness agriculture conducting consolidation farm group; level of self-supporting farmer group up atformal institution (co-operation of association) and revitalization institute of counseling up at CenterService and Consultancy of Agribusiness, which one of the function are mediator and facilitator. Withexpected inwrought effort partner strategy can realize comparative advantage become competitiveadvantage either in local market, exporting and regional.